Art of the Avant-Garde in Russia : Selections from the George Costakis Collection - Rowell, Margit; Zander Rudenstine, Angelica (New York : The Solomon R. Guggenheim Foundation, 1981)
Babichev, Alexei Vasilievich ; Bubnova, Varvara Dmitrievna ; Chashnik, Ilia Grigorevich ; Chekrygin, Vasilii Nikolaevich ; Drevin, Alexandr Davidovich ; Ender, Ksenia Vladimirovna ; Exter, Alexandra Alexandrovna ; Filonov, Pavel Nikolaevich ; Grinberg, Nikolai Ivanovich ; etc.
Art of the Avant-Garde in Russia: Selections from the George Costakis Collection
boek
Keywords: Rusland